THE ANALYSIS OF A TRANSGENDER IDENTITY IN THE NOVEL â€œTHE DANISH GIRLâ€ BY DAVID EBERSHOFF - Saputra, Rizaldi Eko; Bahar, Bahar (Study Program of English Literature, 2020)
This thesis analyzed of transgender identity in the novel â€œThe Danish Girlâ€ by David Ebershoff. It used queer theory as literature approach. The purpose of this research were factors Einar Wegener as the main character in The Danish Girl novel became a transgender and how does the main character life as a transgender depict in this novel. The method of this research was descriptive qualitative method. The source of the data of this research was the novel The Danish Girl by David Ebershoff which was published in 2000 and consists of 29 chapters and 310 pages. While, the instrument of this research was note taking. The technique of the data analysis of this research was linked to the theory, concept, and method. It found two factors that causing being transgender, they are biological factors and environmental factors which environmental factors include family, friends, and doctor. Moreover, the main characterâ€™s life as a transgender depict in this novel shows transition, transgender life, and transforming attitude.